ANALISIS NILAI TAMBAH PRODUK TAHU DARI KEDELAI DI KELURAHAN SUNGAI BESAR KECAMATAN BANJARBARU SELATAN KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Zuraida Zuraida (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
The Purpose of this Study was to Determine the Extent to which the Process of Processing Soybeans into Processed Products,Namely Tofu that can Provide a level of Profit and added Value for Businesses in the Study Area. Data Collection was Done by Purposive Sampling method (Deliberately). The Results showed that the Tofu Processing Process was Carried out Using Simple Technology,Namely Using the Main Raw Material of Soybeans. Mashed with added Vinegar and Salt Acid with a Simple Tool.As for the Amount of Soybean Raw Material once the Production is an Average of 133,33 kg Per day With 226,61kg of Tofu. Workforce 6,90 HOK with Labor out of 0,052 HOK Per kg of Soybeans to Know in Return for Rp 5.460 Added Value of Rp 7.164,02 per kg with a Ratio of Added Value Obtained 42,89 % of the output Value means that Every Rp 100 output Values Will Get an Added Value of 42,89 Which is Include in the Category of High Added Value. Profits are Obtained in the Amount of Rp1 .704,02 with a Ratio of 23,79 % to Added Value. Keywords : Soybean,Tofu, Added Value